"Em pleno coração da Aldeota": usos e conflitos em torno da Praça Portugal - Cunha, Tiago Araújo (2016)
This Master’s thesis investigated the conflict between the city administration of Fortaleza, in Brazil, and members of the group Direitos Urbanos Fortaleza, dedicated to “urban rights”, amid a project of intervention in Portugal Square, announced by the mayor on March 7, 2014. Located at the neighborhood of Aldeota, the square is made up of a central roundabout and four triangles, at the crossing of two major avenues. The project foresaw the roundabout destruction, to open way for a crossing with traffic lights. The works would be initiated shortly after the announcement; instead, controversy and conflict took place for two years, till April 18, 2016. During this time, the research kept track of newspaper articles on the topic, as well as the discussions on the online group forum opposing the municipal project. I have also taken part in meetings and actions of protest defending Portugal Square. Throughout the research it was perceived and analyzed how policies of urban planning are carried out, and the attempts of political participation of civil society in the decision-making process regarding the city. We conclude that the city administration disqualified Portugal Square as a place of leisure and sociability, and used this discourse to justify the intervention, keeping the process in closed cabinet, with limited space for dialogue.